Pemetaan Tanah Sederhana Menggunakan Penginderaan Jauh Remote Sensing di Kawasan Pantai Kelurahan Damon Kabupaten Bengkalis - Jusi, Ulfa; Saily, Randhi; Maizir, Harnedi; Haniza, Sjelly; Hamidi, Ahmad; Karnaidi, Anwar; Nasution, Wahyu Hidayat (Jurnal Pengabdian KOLABORATIF, 2025)
Land mapping in coastal areas is critical for supporting natural resource management and sustainable regional planning. This community service project aims to introduce a simple land mapping method using remote sensing technology with drones on the coast of Damon Village, Bengkalis. Aerial photography was taken at an altitude of 80 meters and the data was processed using ArcGIS software to produce a geospatial map containing boundaries, coastlines, waters, facilities, and infrastructure. This map can be used by village officials for spatial planning and coastal area management. The results of the community service demonstrate that this technology is effective, efficient, and reliable as a basis for decision-making and supports the development of advanced mapping in the future.
Keywords: coastline; land mapping; remote sensing